Research Strategy in Nutrition and Feeding Systems for Meat Goat Production - Simon P Ginting; Leo P Batubara (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
The capability of ruminant animals, including goats to transform the non-food materials into high quality animal proteins for human consumption through a complex digestive and metabolic system put these animals into a unique position in the food- chain system. However, this comparative advantage is not without cost, since when compared to mono-gastric animals, the ruminant is less efficient in producing every unit of protein or energy from each unit of feed they consumed. Therefore, research programme or technology that aims to improve the efficiency of utilization of the various non-food materials by goats should be the priority. Basically, the research programmes in goat feeding and nutrition should be oriented into the real needs of the potential beneficiaries or users. In accordance to this, it is a pre-requisite to identify and to understand the structure and the characteristics of goat production systems that existed. Most of goat production system in Indonesia is typically small scale operation (92%), which operates in a low input system. It is common that under this type of production system, the flow products such as manure or/and kids  are the main goals. Consequently, the stability of feed supply throught the year to at least maintain the existing population become more important than the quality of feeds that fulfill the standard requirement for nutrients. The research programme for this group of goat production should be oriented to (1) developing production system that guarantees the supply  of  feed  throught  the  year;  (2)  maximizing the  potential  benefit  of  the  “compensatory growth”  phenomenon; (3) minimising the effects of anti nutritional factors contained in various forages. Under the commercial production type that operates in a high input system, the final products such as meat is the main goal. Under this production system the rate of productivity of (growth rate, reproduction rate, feed conversion) of individual animas become very important. The research program for this commercial operation should be oriented into (1) developing of various formulae based on non-conventional feeds; (2) optimising rumen function to support maximum fermentative digestion; (3) optimising the protein/energy ratio in the rumen; (4) stimulating the production of glucogenic volatile fatty acid production in the rumen; (5) manipulating the microbial population in the rumen (defaunation); and (6) stimulating the development and colonization of microbial for fiber fermentation.   Key words: Goats, feeding system